Effect of acute and chronic coenzyme Q10 supplementation on creatine kinase after exhaustive aerobic activity - Parvaneh Valadbeigi (International Journal of Biomedicine and Public Health, 2018)
Introduction: Fatigue and muscle ache, is a common and prevalent experience after physical activity, especially exhausting activities. The purpose of this study was to investigate the acute and chronic effects of supplementation of coenzyme Q10 on creatine kinase after exhausting aerobic activity in soccer players.  Methods: Twelve male soccer players who did not have a history of muscular injury since six months ago volunteered to participate in the study. They were examined in three groups of acute, chronic and control. In order to induce muscle damage, a Bruce exhaustive test was performed and to determine the level of creatine kinase blood samples were taken before and after Bruce test. In the acute situation, one day before the Bruce test, two Q10 supplements (each 100 mg) and in chronic situation Bruce''s test was performed after eight weeks of supplementation. To analyze the data, dependent t-test was used at a significant level of P ≤ 0.05. Results: Diagnosis of muscle damage was assessed by measuring the biochemical changes of the creatine kinase enzyme. Statistical analysis showed no significant changes in the level of creatine kinase in acute situation (p>0.05), but there was a significant decrease in chronic supplementation (p